Using Activity Based Approach and Analytical Hierarchy Process in Comprehensive Islamic Financial Plan Construction - Zurina Shafii; Safeza Mohd Sapian; Mahadzir Ahmad (Universiti Sains Islam Malaysia, 2024)
To establish a financial plan, householders need to consider various factors such as the life-cycle stage the householders are in, family status, economic status, economic environment and their objectives and preferences. Several approaches were introduced in order for a systematic application of financial plan to be constructed. The approaches are the personal risk management approach, goal-programming approach, activity-based approach and ratio analysis approach. This paper highlights the use of goal-programming approach and activity based approach in creating comprehensive Islamic financial plan for a client. A hypothetical example is evaluated and recommendations using both approaches are provided. The report for Activity Based approach will contain the activities worksheet for planning and recommendations that will be reflected in the balance sheet in from of assets, liabilities and net worth. In addition, goal programming approach will distinguished between high, medium and low priority of the recommendations that are to be adopted by the clients according to their evaluation. Both approaches lend easy understanding and tracking of clients' fund and records.